2019
DOI: 10.1002/jcp.29037
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide, a cancer chemo drug hampers fibrotic liver regeneration by interrupting oxidative stress rekindling and stellate cell rejuvenation

Abstract: After withdrawal of liver toxic insult, the spontaneous regenerative potential of the liver is well reported in the literature. On the other hand, various molecules have been reported to promote as well as delay such natural regeneration. This current study investigates the involvement of arsenic trioxide (ATO) medication at chemotherapeutic dose on the spontaneous regeneration of the CCl 4 induced fibrotic liver. Liver injury markers, such as albumin and SGOT, SGPT, and ALP activities, in serum indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…For example, arsenic trioxide, a highly toxic mineral, is used for specific medical purposes. Extensive modern pharmacological research has confirmed its effectiveness and safety under certain conditions ( Nithyananthan and Thirunavukkarasu, 2020 ; Guo et al, 2021 ). Of course, the use of these toxic mineral medicines also requires strict adherence to the correct dosage, compatibility, preparation, administration and storage methods to avoid adverse reactions or poisoning events.…”
Section: Conservation Of Animal Resources Through Traditional Practic...mentioning
confidence: 99%
“…For example, arsenic trioxide, a highly toxic mineral, is used for specific medical purposes. Extensive modern pharmacological research has confirmed its effectiveness and safety under certain conditions ( Nithyananthan and Thirunavukkarasu, 2020 ; Guo et al, 2021 ). Of course, the use of these toxic mineral medicines also requires strict adherence to the correct dosage, compatibility, preparation, administration and storage methods to avoid adverse reactions or poisoning events.…”
Section: Conservation Of Animal Resources Through Traditional Practic...mentioning
confidence: 99%
“…Some traditional Chinese medicines were found to contain high arsenic and have been used for more than 3000 years (Huo et al, 2020;Wu et al, 2020). In addition, arsenic induced cells apoptosis is not only the main mechanism of anti-tumor effect, but also one of the main causes of cytotoxic (Wu et al, 2018;Nithyananthan and Thirunavukkarasu, 2020). Therefore, it is of great significance to clarify the damage mechanism of arsenic poisoning and find out the possible regulatory targets (Graphical Abstract).…”
Section: Introductionmentioning
confidence: 99%
“…Among the mechanisms of arsenic induced hepatocyte injury, especially oxidative stress mediated hepatocyte apoptosis that is considered as the core event (Nithyananthan et al, 2020). Arsenious acid [As(III)] is believed mainly responsible for the induction of epidemiological toxicity by the production of reactive oxygen species (ROS) and it also exerts genotoxicity (Jiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Too often, when reporting and comparing experimental outcomes in terms of liver fibrosis stages, the data are treated as continuous variables [16,18,21,22,92]. Fibrosis stage is a category that describes both the amount of LCT quantified on the liver biopsy and the architecture of the connective tissue.…”
Section: Fibrosis Stage Is Not a Continuous Variablementioning
confidence: 99%
“…Mean amount of liver connective tissue in healthy male Wistar rats. Graphs (mean ± two standard errors) of the amount of liver connective tissue quantified on histological sections stained with Masson's trichrome [6,11,12,24,31,40,41,61] (a) or picrosirius red[12,20,[22][23][24]28,35,37,[45][46][47]51,59] (b) revealed significant differences. Multiple graphs within one study represents multiple rat groups within the study.…”
mentioning
confidence: 99%